Mental illness and injuries: emerging health challenges of urbanisation in South Asia - Nambiar, Devaki; Razzak, Junaid Abdul; Afsana, Kaosar; Adams, Alayne M.; Hasan, Arif; Mohan, DInesh; Patel, Vikram H. (© 2017 BMJ Publishing Group, 2018)
This article was published in the BMJ (Online) [© 2017 BMJ Publishing Group] and the definitive version is available at: http://doi.org10.1136/bmj.j1126 The Journal's website is at: http://www.bmj.com/content/357/bmj.j1126